The Role of Paracellular Transport in the Intestinal Absorption and Biopharmaceutical Characterization of Minoxidil - Milica Markovic; Moran Zur; Sapir Garsiani; Daniel Porat; Sandra Cvijić; Gordon L. Amidon; Arik Dahan (MDPI AG, 2022)
The purpose of this study was to evaluate mechanisms behind the intestinal permeability of minoxidil, with special emphasis on paracellular transport, and elucidate the suitability of minoxidil to be a reference drug for Biopharmaceutics Classification System (BCS). The permeability of minoxidil (vs. metoprolol) was evaluated in-silico, in-vitro using both the PAMPA assay and across Caco-2 cell monolayers, as well as in-vivo in rats throughout the entire intestine. The permeability was studied in conditions that represent the different segments of the small intestine: upper jejunum (pH 6.5), mid small intestine (pH 7.0), distal ileum (pH 7.5), and colon (pH 6.5). Since we aimed to investigate the paracellular transport of minoxidil, we have also examined its permeability in the presence of quercetin (250 µM), which closes the tight junctions, and sodium decanoate (10 mM), which opens the tight junctions. While metoprolol demonstrated segmental-dependent rat and PAMPA permeability, with higher permeability in higher pH regions, the permeability of minoxidil was pH-independent. Minoxidil PAMPA permeability was significantly lower than its rat permeability, indicating a potential significant role of the paracellular route. In rat intestinal perfusion studies, and across Caco-2 monolayers, tight junction modifiers significantly affected minoxidil permeability; while the presence of quercetin caused decreased permeability, the presence of sodium decanoate caused an increase in minoxidil permeability. In accordance with these in-vitro and in-vivo results, in-silico simulations indicated that approximatelly 15% of minoxidil dose is absorbed paracellularly, mainly in the proximal parts of the intestine. The results of this study indicate that paracellular transport plays a significant role in the intestinal permeability of minoxidil following oral administration. Since this permeation route may lead to higher variability in comparison to transcellular, these findings diminish the suitability of minoxidil to serve as the low/high BSC permeability class benchmark.